El sistema integrado de administración financiera SIAF-SP y su incidencia en la gestión presupuestal como factor hacia la calidad del hospital III Iquitos de EsSalud Loreto 2023 - Da Costa Rodriguez, Ketty Lenira (2025)
The purpose of this research was to determine whether the Integrated Financial Management System (SIAF-SP) has an impact on management as a factor in the quality of Hospital III Iquitos of EsSalud Loreto, 2023. Opting for a quantitative study with a non-experimental design, the sample consisted of 30 employees involved in the hospital's administrative and budgetary processes. The findings show that there is no significant relationship between the SIAF-SP and quality-oriented management (r=-0.012; p=0.948). Likewise, the tests associated with the budget formulation and process modules, administrative module, and accounting module also showed low correlations with no statistical significance (r=0.029; r=0.189; r=-0.221; p>0.05), indicating that these components of the system do not directly affect institutional quality management.